Science Literacy in Early Childhood: Development of Learning Programs in the Classroom - Choiriyah, Choiriyah (Universitas Negeri Semarang, 2021)
The importance of science literacy in early childhood greatly influences the development of scientific thinking ability. Early childhood is the most critical learning goal that can be done with a student-centered approach to the classroom. This article discusses the needs of science literacy at an early age. Various investigative processes have been carried out by uncovering qualitative methodology. The interview method was conducted to five early childhood teachers. Tenik data analysis using Heurmeutical analysis and Miles and Huberman models. The results showed that early childhood in the application of science literacy as a learning development program in the classroom requires three aspects that need to be considered, namely: attitude, skills, self-competence in children's cognitive, and participation in classroom strategies mapped by teachers. While the needs of learning in the classroom are very important to be done as an effort to improve the competence of teachers to the quality of teaching. In the long term, this research has implications in the field of education, namely the development of teacher competencies on the ability to manage science literacy at an early age.